A rare cause of Brown-Sequard syndrome: A case report and review of literature - Venkatraman, Chandramouleeswaran; Vellachamy, Kannan; Ranganathan, Lakshmi Narasimhan; Samivel, Balasubramanian; Anbazhagan, Ravi Lalapet (Indian Journal of Case Reports, 2020)
The incidence of spinal strokes is 1% of all strokes and spinal strokes presenting as Brown-Sequard syndrome is very rare. The management of spinal strokes needs early investigation which includes magnetic resonance imaging with diffusion-weighted imaging sequence. Patients presenting within 3–5 h of the onset of symptoms have been treated with thrombolysis. For late presentations, early spinal rehabilitation should be initiated to prevent complications. We are reporting the case of a 49-year-old female patient who presented with acute-onset right lower limb monoplegia with sensory symptoms and diagnosed as incomplete Brown-Sequard syndrome due to sulcal artery infarction.